2020
DOI: 10.3389/fphar.2020.579068
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Functions and Clinical Applications of Integrins in Cancers

Abstract: Integrins are the adhesion molecules and receptors of extracellular matrix (ECM). They mediate the interactions between cells-cells and cells-ECM. The crosstalk between cancer cells and their microenvironment triggers a variety of critical signaling cues and promotes the malignant phenotype of cancer. As a type of transmembrane protein, integrin-mediated cell adhesion is essential in regulating various biological functions of cancer cells. Recent evidence has shown that integrins present on tumor cells or tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 119 publications
1
104
0
2
Order By: Relevance
“…Given the wide clinical use of vinca alkaloids and taxanes, currently, the microtubules represent the best target to date for cancer chemotherapy 69 . However, several clinical trials have proved integrins to be a promising therapeutic target to battle cancer cells, though no specific drug was found to be exceptionally effective 71 . We believe the experimental techniques used in our study and the results provided by them to be of aid to develop novel integrin targeting drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the wide clinical use of vinca alkaloids and taxanes, currently, the microtubules represent the best target to date for cancer chemotherapy 69 . However, several clinical trials have proved integrins to be a promising therapeutic target to battle cancer cells, though no specific drug was found to be exceptionally effective 71 . We believe the experimental techniques used in our study and the results provided by them to be of aid to develop novel integrin targeting drugs.…”
Section: Discussionmentioning
confidence: 99%
“… 190 Exosomal tenascin C interacted with integrin α5β1 and αvβ6 on T cells, subsequently attenuated the expression of p-mTOR signaling. 190 , 191 It was worth noting that another study reported that GSCs-derived exosomes did not directly interact with T cells to suppress T cell immune responses, but induced monocytic myeloid-derived suppressor cells and inhibited the maturation of monocytes. 192 When CD14 + monocytes were removed from PBMC, the inhibitory effect of GSCs-exosomes on T cell proliferation could be partially rescued.…”
Section: The Biological Roles Of Cscs-derived Evsmentioning
confidence: 99%
“…This is due to the fact, that the ECM of the TME can be different for certain tumor entities [ 111 ] and for different stages of tumor progression [ 30 ]. Likewise, the role of the ECM receptors is diverse and not entirely defined for each cell type within the TME at any stage of tumor progression and dissemination [ 72 , 75 , 78 , 112 ]. However, the ECM contacts of cells in the TME affect inter alia the secretion and deposition, as well as the remodeling of ECM components.…”
Section: The “Give and Take” Between The Ecm And Cells Within The mentioning
confidence: 99%